Internal Factors Related To The Selection Of Maternity Places For Maternity Mothers At UPTD Puskesmas Aramo, Aramo District, South Nias Regency - Ndruru, Nyaman; Ridesman, Ridesman; Pasaribu, Riska Susanti (CV. Devitara, 2023)
The coverage of maternity assistance by health workers with midwifery competence in 2018 tends to increase, namely in 2017 it reached 86.38%, and in 2014 the coverage of maternity assistance by health workers in Indonesia has reached 96.88%. However, the increasing coverage of birth attendants by health workers in Indonesia has not been matched by an increase in childbirth in health care facilities. The purpose of this study was to analyze internal factors related to the selection of delivery sites for maternity mothers in the working area of Aramo Health Center, Aramo District, South Nias Regency. This research is an analytical survey with a cross sectional design using secondary and primary data. The research was conducted in the working area of Aramo Health Center, Aramo District, South Nias Regency. The population in this study was 311 pregnant women. The sample in this study was 76 third trimester pregnant women using simple random sampling with the slovin formula. Data analysis was performed univariately, bivariately using chi-square. The results showed the selection of a place of delivery at home as many as 44 (57.9%) respondents and the selection of a place of delivery in a health facility as many as 32 (42.1%) respondents, there was a significant relationship between factors (education, work, parity, knowledge, husband/family support and distance) with value (0.001), all of which had a significant relationship with the choice of place of delivery. The conclusion of this study is that all factors related to the choice of place of delivery in III trimester pregnant women have a relationship. Advice is expected to health workers to be able to provide more information to maternity mothers that the importance of giving birth in a health facility.